SISTEM PENDUKUNG KEPUTUSAN PENENTUAN LOKASI PEMASANGANIKLAN AJANG PROMOSI BIMBEL MENGGUNAKAN METODE ANALYTICAL HIERARCHY PROCESS (Studi Kasus: Bimbel Sony Sugema College) - Syamsiah Syamsiah; Puput Irfansyah; Tjipto Djuhartono (JABE (Journal of Applied Business and Economic), 2015)
Decision-making is done in a fast, effective, and accountable to be the key to success in global competition in the future. Having a lot of  information is not enough, if it is unable mixes quickly becoming alternative best alternative in the decision making process, decision support system is an interactive system, which helps decision-makers through the use of data and decision models to solve problems that are semi structured or unstructured. AHP is a decision support models developed by Thomas L. Saaty. Models supporting this decision will spell trouble multi-factor or multi complex criteria into a hierarchy, according to Saaty (1993), the hierarchy is defined as a representation of a complex problem in a structure of multi-level where the first level is a goal, followed by level factors, criteria, sub-criteria, and so on down to the last level of the alternatives. By hierarchy, a complex problem can be decomposed into their groups were then organized into a hierarchical form so that the problem would appear more structured and systematic. The results showed the use of Analytical Hierarchy Process (AHP) as a model for decision support system determining the location of the advertising campaign bimbel sony sugema college can help the team work advertising campaign in prioritization decisions for the implementation of the advertising campaign event through a weighting process multiple criteria and selection more quickly, accurate and more effective.